Workshop Peningkatan Kompetensi Guru dan Tenaga Kependidikan - Indarta Priyana; Antonius Bimo Rentor Luntungan; Fitria Angelia Ridwan; Veronica Rohali Sitorus (Ma'soem University, 2026)
This Community Service (PKM) activity was carried out to improve the competence of teachers and education personnel in Atambua, Belu Regency, East Nusa Tenggara. The main problems faced by partners are limited access to competency development training, low digital literacy, and lack of strengthening soft skills and adaptability in supporting quality education services. This condition is a challenge for educators in the Eastern Indonesia region in dealing with the development of technology-based education and changing learning needs. PKM activities are carried out using participatory training methods through an andragogy (adult learning) approach. The stages of the activity include observation of participant needs, preparation of training materials, implementation of workshops, group discussions, mind mapping practices, learning simulations, and evaluation of activities through pre-test and post-test. Participants in the activity consisted of teachers, principals, and education personnel in Belu Regency. The results of the activity showed that participants experienced an increase in understanding of digital literacy, interpersonal communication, adaptive mindset development, and participatory learning strategies. Participants also showed high enthusiasm during the workshop activities and were able to make a commitment to self-development through the AGILE concept as a form of readiness to face changes in the world of education. This activity has a positive impact on improving the professional competence of teachers and education personnel and supporting the strengthening of the quality of education services in the Eastern Indonesia region.